Ternary Zinc(II) Complex with 2-Amino Benzothiazole and Phenoxyacetic Acid: Synthesis, Crystal Structure and Antimicrobial Activity - Haibin, Gu; Zhiyuan, Wang; Wuyong, Chen (Asian Journal of Chemistry, 2011)
A novel ternary complex of Zn(pa)2(aben)2 (pa = phenoxyacetic acid anion, aben = 2-amino benzothiazole) was synthesized by the reaction of zinc chloride, 2-amino benzothiazole and phenoxyacetic acid. Elemental analysis, IR, 1H NMR, 13C NMR and X-ray single-crystal diffraction were carried out to determine the composition and crystal structure. The complex crystallizes in the monoclinic system, space group C2/c with a = 26.8731(5), b = 30.1325(8), c = 14.9696(4) Å, b = 91.045(2)º, C30H26O6N4S2Zn, Mr = 668.04, V = 12119.7(5) Å3, T = 296(2), Z = 16, Dc = 1.464 mg/mm3, μ(Mo Ka) = 0.998 mm-1, F(000) = 5504, 26154 reflections measured, 12378 unique (Rint = 0.0196) which were used in all calculations. The final wR(F2) was 0.0869 (all data). The Zn(II) atom is four-coordinated with two carboxylate oxygen atoms of the two phenoxyacetic acid and two nitrogen atoms in thiazole rings of the two 2-amino benzothiazole. The analysis of crystal structure shows that there are intermolecular and intramolecular hydrogen bonding between amino-nitrogen atoms of the two 2-amino benzothiazole and carboxylate-oxygen and ether-oxygen atoms of the two phenoxyacetic acid. The antimicrobial properties of the title complex and the ligands i.e., phenoxyacetic acid and 2-amino benzothiazole were tested against representative bacterial and fungal strains. Results show that it exhibits excellent inhibitory effect against the tested bacteria, yeasts and moulds, which is better than that of its two free ligands.